Corrosion behavior of ST37 low carbon steel welded joints in acidic and basic environments: implications for structural durability - Andika Wisnujati; Mudjijana; Syamsul Ma’arif; Satriardi; Hojjat Bagban (Universitas Muhammadiyah Magelang, 2026)
This study investigates the corrosion behavior and mechanical degradation of welded ST37 low-carbon steel exposed to basic (NaOH) and chloride-containing (NH₄Cl) environments. The objective is to evaluate the influence of solution chemistry and immersion time on corrosion rate, surface morphology, elemental composition, and tensile properties of welded steel structures. Welded ST37 specimens were immersed in 1 M NaOH and 1 M NH₄Cl solutions for 100, 200, and 300 hours under controlled laboratory conditions. Corrosion rates were determined using the weight loss method, while surface morphology and elemental composition were analyzed using scanning electron microscopy coupled with energy dispersive spectroscopy (SEM–EDS). Mechanical degradation was evaluated through tensile testing following ASTM E8 standards. The results show that NaOH exposure promotes the formation of a stable oxide layer that reduces corrosion rates from 0.024 to 0.019 mm/year and partially restores tensile strength after prolonged immersion. In contrast, NH₄Cl exposure causes more aggressive corrosion characterized by pitting, porous corrosion products, and localized surface degradation due to chloride-induced passive film breakdown. SEM observations confirm thicker corrosion layers and localized attack in the weld metal region, while EDS analysis reveals increased oxygen and chloride content associated with the respective corrosion mechanisms.